How Misattribution of External Factors Can Lead to Biased Human Resource Management - Frollová, Nikola; Houdek, Petr, 1981-; Bahník, Štěpán; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2023)
Randomness is not often perceived as a causal factor of the success or failures of employees and their teams. This dissertation shows several consequences of ignoring random shocks for group and individual decision-making and self- assessment. In a series of three studies, I demonstrate how good or bad performance can easily be misinterpreted due to attribution biases such as self- serving bias or preference for maintaining control over the process, which can lead to overconfidence and inadequate attribution of merit. These findings contribute to the fields of performance management evaluation and organizational learning practices by showing the limits of some performance indicators due to bounded rationality problems.
Vedoucí práce: Petr Houdek
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2023
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2023
Způsob přístupu: Internet
Keywords: podniková ekonomika a management [obor disert. práce]; disertace; dissertations